Efficiency increase of e‐learning by applying on‐line intelligence computer learning systems - Ginevičius, Romualdas; Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras (Journal of Business Economics and Management, 2003)
Based on the analysis of existing computer learning, neural networks, information, expert and decision support systems, the following e‐learning systems were developed by authors: construction, real estate, facilities management, international trade, ethics, innovation, sustainable development, building refurbishment, etc. Application of above multiple criteria computer learning systems developed by authors allows one to determine the strengths and weaknesses of analysed alternatives and its constituent parts. Calculations were made to find out by what degree one version is better than an other and the reasons disclosed why it is namely so. Landmarks are set for an increase in the efficiency of versions, etc.First Published Online: 14 Oct 2010